Ephemeral Feminist Histories and the Politics of Transmission within Digital Culture. Issue 5 (3rd September 2017) - Withers, Deborah
ABSTRACT: This article uses the work of Bernard Stiegler to understand how widespread digitisation has influenced the transmission of ephemeral and marginalised feminist histories and archives, using as a case study my experience of creating a low-budget feminist digital archive in the first decade of the twenty-first century, the Women's Liberation Music Archive (WLMA). I explore how the WLMA benefitted from unique transmission conditions enabled by digitisation, namely widened access to recorded matter that had become inoperable within feminist communities, technically, socially and culturally. I then go on to examine two areas that pose both threats and possibilities for the sustainability of digital archives in the long term. The first issue relates to the position of low-financed digital archives within the volatile dynamics of change that propel the innovation-driven market economy. The second relates to metadata and how digital technologies present an opportunity to re-think the terms of categorisation used to describe information within networks of association and reference. Finally, I argue that acquiring the technical skills to take care of digital information will perform a key role ensuring digital archives can survive in the long term.